Robert B. Parker's old black magic - Parker, Robert B., 1932-2010; Atkins, Ace (Parker, Robert B., 1932-2010. Spenser novel., 2018)
"Iconic, tough-but-tender Boston PI Spenser delves into the black market art scene to investigate a decades-long unsolved crime of dangerous proportions. The heist was legendary, still talked about twenty years after the priceless paintings disappeared from one of Boston's premier art museums. Most thought the art was lost forever, buried deep, sold off overseas, or, worse, destroyed as incriminating evidence. But when paint chips from the most valuable piece stolen, Gentlemen in Black by a Spanish master, arrives at the desk of a Boston journalist, the museum finds hope and enlists Spenser's help. Soon the cold art case thrusts Spenser into the shady world of black market art dealers, aged Mafia bosses, and old vendettas. A five-million-dollar-reward by the museum's top benefactor, an aged, unlikable Boston socialite, sets Spenser and pals Vinnie Morris and Hawk onto a trail of hidden secrets, jailhouse confessions, and decades-old murders. Set against the high-society art scene and the low-life back alleys of Boston, this is classic Spenser doing what he does best"--